A 21-Year Perspective on Occupational Skin and Respiratory Diseases Among Food Handlers - Granzotto, Jessica; Lazzarato, Ilaria; Mauro, Marcella; Cegolon, Luca; Larese Filon, Francesca (La Medicina del Lavoro, 2025)
Background: Food handlers may have an increased risk of developing occupational skin and respiratory diseases. Methods: This retrospective study was based on examinations, skin prick testing, and patch testing performed at the Unit of Occupational Medicine at the University of Trieste (N-E Italy) between 2002 and 2022 in food-handler workers referred to the unit for suspected occupational allergic diseases. Results: More than half of the population (58.1%) experienced occupational skin diseases, with a higher prevalence among women (OR 3.3, 95% CI 1.5-7.6). Irritant contact dermatitis was the most prevalent skin condition (22.9%), followed by allergic contact dermatitis (20%) and protein contact dermatitis (15.1%). Pastry makers and bakers exhibited a high rate of protein contact dermatitis (20.6 and 17.7%, respectively), which was primarily attributed to wheat flour. Of the participants, 47.8% reported having rhinitis, and 17.6% reported having asthma. Positive SPT results were observed in 34.4% of workers with rhinitis and 58.3% of those with asthma, with bakers and pastry makers being more frequently sensitized to wheat flour (22.8% and 20.6%, respectively). Cooks reported rhinitis (43.2%) and asthma (12.3%) with sensitization to soy, scampi, peanuts, and other foods. Atopy determined by prick test was significantly linked to respiratory symptoms. Bakers and pastry makers showed significantly higher sensitivity to wheat flour (OR 3.3, 95% CI 1.3-7.8). Conclusions:  Food handlers can experience occupational skin and respiratory diseases, and more efforts are needed to prevent such diseases by improving preventive habits and avoiding exposure to allergens.